2013 21st Signal Processing and Communications Applications Conference (SIU) 2013
DOI: 10.1109/siu.2013.6531593
|View full text |Cite
|
Sign up to set email alerts
|

Image resolution enhancement by using interpolation followed by iterative back projection

Abstract: Abstract-In this paper, we propose a new super resolution technique based on the interpolation followed by registering them using iterative back projection (IBP). Low resolution images are being interpolated and then the interpolated images are being registered in order to generate a sharper high resolution image. The proposed technique has been tested on Lena, Elaine, Pepper, and Baboon. The quantitative peak signal-to-noise ratio (PSNR) and structural similarity index (SSIM) results as well as the visual res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…[2][3][4][5] The basic idea behind SR methods is to recover/estimate one or more high resolution (HR) image(s) from one or more low resolution (LR) images. 6,7 Huang and Tsai 8 as pioneers of SR proposed a method to improve the spatial resolution of satellite images of earth, where a large set of translated images of the same scene are available. They showed that SR, using multiple offset images of the same scene and a proper registration, can produce better HR images compared with spline interpolation.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] The basic idea behind SR methods is to recover/estimate one or more high resolution (HR) image(s) from one or more low resolution (LR) images. 6,7 Huang and Tsai 8 as pioneers of SR proposed a method to improve the spatial resolution of satellite images of earth, where a large set of translated images of the same scene are available. They showed that SR, using multiple offset images of the same scene and a proper registration, can produce better HR images compared with spline interpolation.…”
Section: Introductionmentioning
confidence: 99%
“…The main idea of using SVD in [2] for image equalization comes from this fact that Σ A contains the intensity information of the given image [15]. Wavelets have been used quite frequently as tools in many image processing applications such as feature extraction [16], compression [17], [18], face recognition [19], [20], image super resolution [2], [21], [22], and medical image enhancement [23]. The decomposition of images into different frequency ranges permits the isolation of the frequency components into certain subbands [24].…”
Section: Introductionmentioning
confidence: 99%
“…For surveillance videos in real-world scenarios spatial domain approaches are more suitable as they can cope with the complicated motion structures of objects in the scene. These algorithms are generally divided into two groups: single-image-based and multipleimage-based super-resolution algorithms [1], [2].…”
Section: Introductionmentioning
confidence: 99%